Level of Elementary School Students Physical Fitness - Arti Kurniaty Bangun; Sri Syahputri; Yoki Afriandy Rangkuti (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
The absence of data about the level of physical fitness of SD Negeri 054936 Wonorejo students is what inspired this study. The objective of this research was to determine how well the Class V students at SD Negeri 054936 Wonorejo Academic Year 2021/2022 were physically active. There is quantitative descriptive research in this study. A survey was the research method used. The Indonesian Physical Fitness Test (TKJI) for children ages 10 to 12 served as the study's primary data collection tool. Students in the fifth grade at SD Negeri 054936 Wonorejo for the 2021–2022 academic year made up the population of this study. 39 students were selected using the saturation sampling method to determine the sample. Quantitative descriptive analytical techniques using percentages are used in data analysis. Based on the results of the study on the physical fitness of fifth-graders at SD Negeri 054936 Wonorejo for the 2021–2022 Academic Year, there are three students in the excellent category with a percentage of 7.7%, six students in the good category with a percentage of 15.4%, ten students in the average category with a percentage of 25.6%, 17 students came into the less good category, with a percentage of 43.6%, while 3 students fell into the extremely unfortunate category, with a percentage of 7.7%. Therefore, it can be determined from this study that Class V students at SD Negeri 054936 Wonorejo fall into the less group for their level of physical fitness for the 2021–2022 Academic Year. These recommendations are made by the authors in light of the test results in this study: By restricting their use of Android phones, increasing their physical activity, and eating healthier foods, students can improve their physical fitness and become even better.